Evaluation of Vitamin D and Anti-Müllerian Hormone Levels inIraqi Infertile Women - Mohialdeen, Sura Khairialdeen; Hasan, Zainab M Ali; Hussein, Ban Ali (Kesmas, 2022)
Although the mechanism underlying the relationship between vitamin D insufficiency and reproduction is unknown, research suggests that it may have a direct deleterious impact on ovarian function. This is primarily because vitamin D insufficiency can affect gonadal function. The anti-müllerian hormone (AMH) is one of the most important biomarkers produced by granulosa cells and plays a key role in folliculogenesis. This study wanted to look at and compare vitamin D and AMH levels in infertile and fertile women, as well as the relationship between them in both groups. A hundred infertile and fertile women participated in the study. Anti-müllerian, prolactin, follicle-stimulating, and luteinizing hormones, as well as 25 hydroxyvitamin D, were estimated. Vitamin D deficiency was found in 72% of infertile women (n = 36), compared to 48% (n = 24) of the fertile group. There was no significant link between 25-hydroxyvitamin D and AMH in both groups. Infertile women exhibited a significantly lower serum AMH and higher body mass index. This study's findings suggested that the correlation between vitamin D and ovarian reserve markers was unlikely to present. However, the infertile group has a more significant vitamin D deficiency and insufficiency rate.